The Human Factor in the Passenger Boarding Process at the Airport. (2017) - Kierzkowski, Artur; Kisiel, Tomasz
Abstract: The article presents the currently considered strategies of boarding passengers at airports with the use of jetway, showing their advantages and disadvantages. The aim of the paper was to present the human factor, which has not been well discussed yet, and, as the article shows, can have an important influence on the process of carrying out the boarding of passengers. The article presents the results of studies on low-cost airlines passengers. The analysis covered the time needed to place items in the baggage compartments, which depends on the availability of seats and occupancy of the aircraft. The occurrence of seat and aisle interferences was also analysed. In addition, the influence of the boarding passes controlled by the cabin crew on the process of passenger boarding was shown. The data presented can become a basis for developing a new strategy for boarding passengers with the use of a jetway.